Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan : (Studi Kasus Pada PT. Albea Rigid Packaging Surabaya) - Siti Aisah; Yuri Triono (Jurnal Simki Economic, 2023)
PT Albea Rigid Packaging Indonesia is a halal cosmetic packaging manufacturer that must prepare its human resources in order to improve company performance in the cosmetic industry. The purpose of this study is to measure how much "The Influence of Motivation and Work Discipline on Employee Performance at PT Albea Rigid Packaging Surabaya". The type of research used in this research is quantitative. According to Sugiyono (2014) the research method is a scientific way of obtaining valid data with the aim of discovering, proving, and developing knowledge so that in turn it can be used to understand, solve, and anticipate problems in business. Variables of work motivation and work discipline affect employee performance, both of which have a P value below 0.05 so that it can be stated to have a significant influence so that work motivation and work discipline affect employee performance at PT Albea Rigid Packaging Surabaya. On the work motivation variable, where the indicator of the need for encouragement to achieve the goal has the lowest value, it means that employees lack motivation from the leadership regarding their future targets as employees towards career paths.